Attack and interception in networks - Francis Bloch; Kalyan Chatterjee; Bhaskar Dutta (Theoretical Economics, 2023)
This paper studies a game of attack and interception in a network, where a single attacker chooses a target and a path, and each node chooses a level of protection. We show that the Nash equilibrium of the game exists and is unique. We characterize equilibrium attack paths and attack distributions as a function of the underlying network and target values. We show that adding a link or increasing the value of a target may harm the attacker - a comparative statics effect which is reminiscent of Braess's paradox in transportation economics. Finally, we contrast the Nash equilibrium with the equilibria of two variations of the model: one where all nodes cooperate in interception and one where nodes update their beliefs and make inspection decisions upon observing the arrival of a suspicious object.
Keywords: D85; C72; K42; 330; attack and defense; inspection games; Network interdiction; networks